Cigarette Smoking and Urinary Organic Sulfides - Jian, Le; Cao, W. (Elsevier, 2000)
In order to observe how cigarette smoking influences levels of thio-thiazolidine-4-carboxylic acid (TTCA), high performance liquid chromatography (HPLC) was used to detect TTCA in urine from 18 healthy male volunteers. At the same time, the total amount of urinary organic sulfides was determined by the iodine azide test (IAT). Nine of the volunteers had smoking histories (5 to 10 cigarettes per day, as the smoking group), and the rest only occasionally smoke (1 to 2 cigarettes per month, as the control group). Samples were collected in the early morning (limosis) and 90 minutes after smoking a cigarette. Results showed that smoking a single cigarette could elevate the level of urinary organic sulfides both in the smoking and control groups, while a smoking habit appeared to have no significant influence on the urinary organic sulfide level. No significant cumulative effect of cigarette smoking on urinary organic sulfides was found. The influence of cigarette on urinary organic sulfides was temporary. The results suggest that cigarette smoking might be a confounding factor in biomonitoring the levels of carbon disulfide in exposed workers.